Acute eosinophilic pneumonia in the deployed military setting. (April 2018) - Sine, Christy R.; Hiles, Paul D.; Scoville, Stephanie L.; Haynes, Ralph L.; Allan, Patrick F.; Franks, Teri J.; Morris, Michael J.; Osborn, Erik C.
Abstract: Rationale: Acute eosinophilic pneumonia (AEP) is a rare but important cause of severe respiratory failure most typically caused by cigarette smoking, but can also be caused by medications, illicit drugs, infections and environmental exposures. There is growing evidence that disease severity varies and not all patients require mechanical ventilation or even supplemental oxygen. Objectives: To compare patients with AEP treated at Landstuhl Regional Medical Center (LRMC) to those in other published series, and to provide recommendations regarding diagnosis and treatment of AEP. Methods: A retrospective chart review was completed on forty-three cases of AEP which were identified from March 2003 through March 2010 at LRMC, Germany. Results: Tobacco smoking was reported by 91% of our patients. Only 33% of patients in our series had a fever (temperature > 100.4 °F) at presentation. Peripheral eosinophilia (>5%) was present in 35% on initial CBC, but was seen in 72% of patients during their hospital course. Hypoxemia, as measured by PaO2/FiO2 ratio, seemed to be less severe in patients with higher levels of bronchoalveolar (BAL) eosinophilia percentage. Conclusions: Based on our experience and literature review, we recommend adjustments to the diagnostic criteria which may increase consideration of this etiology for acute respiratory illnesses as well as provide clinical clues we have found particularly helpful. Similar to recent reports of initial peripheral eosinophilia correlating with less severe presentation we found that higher BAL eosinophilia correlated with less severe hypoxemia. Highlights: Fever and hypoxemia are absent in 20% of reported cases of AEP. AEP should be more inclusive than a strict 25% BAL eosinophilia cut off. A higher BAL eosinophilia correlates to less severe hypoxemia. Corticosteroid courses can be safely shortened to 2–4 weeks in most cases.